The Concept of Health in Elderly People: A Literature Review - Asadi Noghabi A; Alhani F; Peyrovi H (Iran University of Medical Sciences, 2012)
Background ;Aim : The elderly population is increasing day by day. So it is essential to attend to the health status of this age group for their health promotion and disease prevention. Accordingly having a clear definition of health concept in aged people is necessary.   Material ;Methods : In this study, a comprehensive and in-depth narrative review was carried out by searching the data bases of SCOPUS, PUBMED, PROQUEST, SCIENCE DIRECT, ISC, IRANDOC, MAGIRAN with the key words of "health, the elderly wellbeing, health measurement, health assessment and health status" alongside with the words, "elderly, aging, old people" without limitation of years.   Results: The main approaches toward the concept of health according to available literature were medical and functional models. The medical model holds that physical examination is required for determining the health and wellbeing of elderly people and their health-related needs and the functional model proposes that the things expressed by an elderly can be the best index for their health status and their required supportive systems. It has been indicated that the perceived health by elderly people is a global and useful index which shows their health level and also interacts with social and biological components.   Conclusion : The exploration of health and wellbeing among elderly people has a more mental nature than other age groups. Consequently, the investigation of wellbeing among the elderly must not only be restricted to its medical aspects.  Received: 15 Sep 2012   Accepted: 10 Dec 2012